Boon or bane of advance tax rulings as a measure to mitigate tax uncertainty and foster investment - Markus Diller; Pia Kortebusch; Georg Schneider; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
Tax uncertainty often negatively affects investment. Advance tax rulings (ATRs) are commonly used as a measure to provide tax certainty. Rulings are currently controversially discussed in the context of tax planning activities of multinational firms (Luxembourg Leaks). We analyze ATRs as tax uncertainty shields from both the taxpayers' and the tax authorities' perspectives. In general, tax authorities charge ATR fees and investors request ATRs provided the fee does not exceed a certain threshold. We assume risk neutral investors and that tax authorities integrate investors' reasoning in their decision on whether and at what price to offer ATRs. We find for uniformly distributed cashflows that tax authorities offer ATRs at a prohibitively high fee. However, extending our model framework we find that ATRs are offered if the ATR enables tax authorities either to significantly reduce their tax audit costs, or to increase the probability of detecting ambiguous tax issues, or to increase their revenues by attracting more investment. ATRs may foster investment and are hence potentially beneficial for both tax authorities and taxpayers if the investment projects in question generate relatively small net returns but high tax uncertainty. This pattern is typical for aggressive tax planning strategies, e.g., in tax havens. Our findings are threefold. First, we find that even risk neutral investors will pay for tax certainty. Second, they enable us to explain the enormous demand for rulings for tax-aggressive strategies and illustrate the tax authorities' opportunity cost of offering ATRs free of charge to attract taxaggressive foreign MNGs. Third, our results provide new explanations for why ATRs, even if the fee is rather low, are not as frequently requested by taxpayers with substantial investments, as expected in settings with high tax uncertainty. Our paper elaborates the theoretical foundation that is essential when planning to use ATR fees as a new measure for tax uncertainty in future empirical tests.
Keywords: H21; H25; M41; M42; M48; 330; Advance Tax Rulings; Fee Design; Investment Effects; Tax Aggressiveness; Tax Planning; Tax Risk; Tax Rulings; Tax Uncertainty